2020
DOI: 10.1088/1755-1315/596/1/012023
|View full text |Cite
|
Sign up to set email alerts
|

Effects on MAPP Compatibilizer on Mechanical Properties of Kenaf Core Fibre/Graphene Nanoplatelets reinforced Polypropylene Hybrid Composites

Abstract: Natural fibre has high potential to be used as reinforcement due to more save, greener and environmentally friendly compared to synthetic fibre. In this research, kenaf core fibre (KCF)-graphene nanoplatelets (GNP) reinforced polypropylene (PP) composites were melt blending using Brabender internal mixer and fabricated by compression moulding. This research aims to fabricate and study the effect of different amounts of MAPP on the mechanical properties of the PP/KCF/GNP composites. The difference amount of mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
0
0
Order By: Relevance
“…Thus, it cannot be concluded that increasing composition of MAPP compatibiliser is directly proportional to improve the composite flow or viscosity. A study conducted by Sabri et al, [18] varying MAPP between 1-7 wt.% in kenaf/graphene/PP composite showed fluctuation of percent in elongation at break indicating that the addition of MAPP has no direct effect on the flow or softening of the composite. Junaedi et al, [19] found that addition MAPP in short carbon fibre/PP composite up to 15 wt.% loading increases the ductility, however at 35 wt.% loading has no change in ductility but slightly drop in strength and modulus.…”
Section: Melt Flow Indexmentioning
confidence: 98%
“…Thus, it cannot be concluded that increasing composition of MAPP compatibiliser is directly proportional to improve the composite flow or viscosity. A study conducted by Sabri et al, [18] varying MAPP between 1-7 wt.% in kenaf/graphene/PP composite showed fluctuation of percent in elongation at break indicating that the addition of MAPP has no direct effect on the flow or softening of the composite. Junaedi et al, [19] found that addition MAPP in short carbon fibre/PP composite up to 15 wt.% loading increases the ductility, however at 35 wt.% loading has no change in ductility but slightly drop in strength and modulus.…”
Section: Melt Flow Indexmentioning
confidence: 98%